Hubungan Pengetahuan Dan Sikap Dengan Perilaku Berisiko Seks Bebas Anak Jalanan Di Rumah Singgah Kota Klaten - Ningsih, Diah Ismalastia; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Reproduction health conditions on street children behave when promiscuity is a problem that urgently need special attention. The behavior of street children occur because of lack of precise information, thus providing the knowledge and attitude of one of the street children and street children in behavior could not consider the risks or impacts that would occur eg unwanted pregnancy, abortion and sexually transmitted diseases The purpose of this study was to determine the relationship between knowledge and attitude with sexual risk behaviors street children in shelter homes Klaten town. This research method using observational design with cross sectional approach. The population in this study are all street children are enrolled in Klaten town halfway house as many as 40 children who have the criteria of age between 10 years to 24 years. The sample selection using the total sample with a sample of 40 people. Statistical test using Chi Square. The results show that there is a relationship between knowledge (pvalue = 0.018 <0.05) and there is no relationship between attitude (pvalue = 5.53> 0.05), with free sex risk behaviors of street children in the house shelter city klaten